Funding policies and post-abortion long-acting reversible contraception: Results from a cluster randomized trial - ROCCA, Corinne H (Am J Obstet Gynecol, 2015)
BACKGROUND: Almost half of women having an abortion in the United States have had a prior procedure, highlighting a failure to provide adequate preventive care. Provision of intrauterine devices and implants, which have high upfront costs, can be uniquely challenging in the abortion care setting. OBJECTIVE: We conducted a study of a clinic-wide training intervention on long-acting reversible contraception and examined the effect of the intervention and contraceptive insurance coverage and funding policies on use of long-acting contraceptives post-abortion. STUDY DESIGN: This sub-analysis of a cluster, randomized trial examines data from the 648 abortion patients recruited from 17 reproductive health centers across the United States. The trial followed participants aged 18-25 who did not desire pregnancy for a year. We measured the effect of the intervention, health insurance, and funding policies on contraceptive outcomes, including intrauterine device and implant counseling and selection at the abortion visit, using logistic regression with generalized estimating equations for clustering. We used survival analysis to model actual initiation of these methods over one year. RESULTS: Women obtaining abortion care at intervention sites were more likely to report intrauterine device and implant counseling (70% vs. 41%, aOR, 3.83; 95% CI, 2.37-6.19) as well as selection of these methods (36% vs. 21%, aOR, 2.11; 95% CI, 1.39-3.21). However, actual initiation of methods was similar between study arms (22/100 woman-years each, aHR, 0.88; 95% CI, 0.51-1.51). Health insurance and funding policies were important for initiation of intrauterine devices and implants. Compared to uninsured women, those with public health insurance had far higher initiation (aHR, 2.18; 95% CI, 1.31-3.62). Women at sites that provide state Medicaid enrollees abortion coverage also had higher initiation (aHR, 1.73; 95% CI, 1.04-2.88), as did those at sites with state mandates for private health insurance to cover contraception (aHR, 1.80; 95% CI, 1.06-3.07). Few of the women with private insurance used it to pay for the abortion (28%), but those who did initiated long-acting contraceptive methods at almost twice the rate as women who paid for it themselves or with donated funds (aHR private, 1.94; 95% CI, 1.10-3.43). CONCLUSIONS: The clinic-wide training increased long-acting reversible contraceptive counseling and selection, but did not change initiation for abortion patients. Long-acting method use post-abortion was strongly associated with funding. Restrictions on coverage of abortion and contraceptives in abortion settings prevent initiation of desired long-acting methods.